2010
DOI: 10.1242/jeb.020792
|View full text |Cite
|
Sign up to set email alerts
|

A behavioral perspective on the biophysics of the light-dependent magnetic compass: a link between directional and spatial perception?

Abstract: Summary In terrestrial organisms, sensitivity to the Earth's magnetic field is mediated by at least two different magnetoreception mechanisms, one involving biogenic ferromagnetic crystals (magnetite/maghemite) and the second involving a photo-induced biochemical reaction that forms long-lasting, spin-coordinated, radical pair intermediates. In some vertebrate groups (amphibians and birds), both mechanisms are present; a light-dependent mechanism provides a directional sense or ‘compass’, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 100 publications
(170 reference statements)
3
74
0
Order By: Relevance
“…As noted above, a lightindependent, magnetite-based compass has also been reported in microphthalmic echolocating bats (Wang et al, 2007;Holland et al, 2008). By contrast, recent evidence suggests that the magnetic compass of epigeic rodents such as the Siberian hamster, Phodopus sungorus, and C57BL/6J mice has more in common with birds than with mole rats; most notably it seems to be disrupted by low-level fields oscillating in the MHz range (Phillips et al, 2010) Phillips, unpublished). These findings point to an intriguing possibility that two fundamentally different mechanisms, namely a light-independent, magnetite-based mechanism (for reviews, see Kirschvink et al, 2001;Winklhofer and Kirschvink, 2010) and a light-induced, photoreceptor-based mechanism (Ritz et al, 2000), underlie magnetic compass orientation in rodents.…”
Section: Two Magnetic Compass Mechanisms In Mammals?mentioning
confidence: 88%
“…As noted above, a lightindependent, magnetite-based compass has also been reported in microphthalmic echolocating bats (Wang et al, 2007;Holland et al, 2008). By contrast, recent evidence suggests that the magnetic compass of epigeic rodents such as the Siberian hamster, Phodopus sungorus, and C57BL/6J mice has more in common with birds than with mole rats; most notably it seems to be disrupted by low-level fields oscillating in the MHz range (Phillips et al, 2010) Phillips, unpublished). These findings point to an intriguing possibility that two fundamentally different mechanisms, namely a light-independent, magnetite-based mechanism (for reviews, see Kirschvink et al, 2001;Winklhofer and Kirschvink, 2010) and a light-induced, photoreceptor-based mechanism (Ritz et al, 2000), underlie magnetic compass orientation in rodents.…”
Section: Two Magnetic Compass Mechanisms In Mammals?mentioning
confidence: 88%
“…True navigation implies that animals orient themselves by relying on cues available at the unfamiliar release site, and these usually are cues with a worldwide geographic distribution such as magnetic cues (Wiltschko and Wiltschko 1995;Lohmann 1991), lightdependent cues (Muheim et al 2006;Phillips et al 2010), infrasound cues (Hagstrum 2000), or odor cues (Jorge 2011;Wallraff 2005). In Experiment 3, we showed that adult L. pholis were able to orient themselves toward their home areas even if they were placed in an unfamiliar distant area, and they did so by relying on cues available in the unfamiliar area (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to current theory, birds may perceive the magnetic field as a three-dimensional pattern superimposed on their visual field (e.g. [80,81,86]). If PL reception takes place in parallel to magnetoreception, we would therefore expect an equally high resolution also for this system.…”
Section: Discussionmentioning
confidence: 99%